Target neonatal echocardiography as efficiency assessment method of shock therapy in newborns (a series of clinical observations) - A. A. Zadvornov; A. A. Chernykh; E. V. Grigoriev; А. А. Rudakova (Вестник анестезиологии и реаниматологии)
The objective was to demonstrate clinical cases of shock therapy in newborns under the control of target neonatal echocardiography. This method of hemodynamic monitoring is performed at the bedside by intensive care physicians and is available around the clock.Materials and methods. The article describes three clinical cases of shock in newborns whose hemodynamic status was assessed by target neonatal echocardiography.Results. The use of target neonatal echocardiography made it possible to identify a disturbed component of hemodynamics (preload, contractility, postload). In some cases, the actual hemodynamic status differs from the hypothetical one. This made it possible to carry out targeted hemodynamic management and prevent pathogenetically unjustified therapy with potential iatrogenic complications.Conclusion. Target neonatal echocardiography has demonstrated its clinical effectiveness in bedside assessment of hemodynamics in critically ill newborns.